Мектеп жасына дейінгі балаларды тіл мəдениетіне баулу жолдары - Омиртаева, Е.Ш. (My University, 2016)
Today, the problem of language development of preschool children remains one of the most important. The article indicated the direction for the development of the sound of speech of preschool children. At the same time it shows the types of work, use of materials and literature folklore.
Keywords: Speech development; sound culture; specific sounds; speech defects